PENGARUH LIKUIDITAS DAN MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PADA CV. MITRA KARYA MEDAN - Ningsih Ani Zebua; Reza Septriawan (Worksheet : Jurnal Akuntansi, 2021)
To assess the company's finances, a profitability ratio can be used. Profitability isthe company's ability to earn a profit in relation to sales, total assets and owncapital. For companies, the problem of profitability is very important because itcan include other ratios, including the ratio of liquidity and working capital.Liquidity is the company's ability to meet short-term obligations smoothly and ontime. The level of liquidity of the company can be shown by liquid assets that areeasily converted into cash, including cash, bank, accounts receivable, marketablesecurities, and inventories. Working capital is a fund needed so that companyoperations can run smoothly in accordance with the policies that have beendetermined for the achievement of company goals. The formulation of the problemin this study is how the influence of liquidity and working capital managementeither partially or simultaneously on profitability at CV. Mitra Karya Medan ?. Theresearch objective was to determine and analyze the effect of liquidity and workingcapital management either partially or simultaneously on profitability at CV. MitraKarya Medan. This study uses multiple linear regression analysis, determinationtest and t test, with the help of the SPSS test tool. Based on the research results, itis known that there is a partial effect of the current ratio on the net profit margin atCV. Mitra Karya Medan, this is shown from the results of the t test where t count>t table (4.807> 2.13185) so that H0 is rejected and Ha is accepted, which meansthat the current ratio variable has a significant (significant) effect with the net profitmargin variable. In addition, there is a partial effect of the debt to equity ratio onthe net profit margin at CV. Mitra Karya Medan, this is shown from the results ofthe t test where t count> t table (3.064> 2.13185) so that H0 is rejected and Ha isaccepted, which means that the debt to equity ratio variable has a significant(significant) effect with the net profit margin variable. Based on the researchresults, it is known that there is an effect of the current ratio and the debt to equityratio simultaneously on the net profit margin at CV. Mitra Karya Medan, and thepercentage of the relationship between the current ratio variable (X1) and the debtto equity ratio (X2) to the net profit margin (Y) is 34.2%, while the remaining 65.8%is influenced by other factors not examined